Hypertensive crises in primary arterial hypertension - cardiovascular system status and central hemodynamics features - V. A. Lusov; E. M. Evsikov; Yu. M. Mashukova; R. A. Sharipov (Российский кардиологический журнал, 2007)
То investigate cardiovascular system damage, as well as changes in intracardial and central hemodynamics, a complex clinical, biochemical, and instrumental examination was performed in 563patients (189 men, 374 women aged 19-67years) suffering from Stage I-III primary arterial hypertension, AH (WHO classification, 1997) and hospitalized with hypertensive crise diagnosis. Comparison group included 619 patients (207 men, 412 women aged 25-66 years) with primary AH of similar severity. In the first 1-2 days after hospitalization, clinical, biochemical, and central hemodynamics parameters (by tetrapolar rheography) were examined. At days 3-7, echocardiography, radiocardiography, ophthalmoscopy were performed; at days 18-22, central hemodynamics parameters were re-assessed in some participants. In more than 50 % of the patients with hypertensive crises, crise development was directly linked to stressors, chronic psychological problems, and central nervous system disturbances, manifested in mioconvulsive syndrome. During the crise, central hemodynamics was characterized by hyperkinetic circulation type, increased cardiac output and heart rate, elevated systolic blood pressure (BP) and поп-significant BP gradient for both arms. These features were observed for 2-5 days and disappeared by days 18-22, with one exception - systolic BP elevation. Central hemodynamics changes were not accompanied by differences in the structure of chronic cardiovascular pathology, frequency and type of left ventricular hypertrophy, electrocardiogram changes, and retinopathy progression inpatients with or without hypertensive crises. For participants with frequent crises, thoracic aorta remodeling, retinopathy, increased total peripheral resistance, and high BP gradient for both arms were less typical than for individuals with rare crises.